Awareness and Practices in Designing and Implementing Development Projects Among Secondary School Teachers Towards Coaching and Mentoring Projects - Tacotaco, Sherilene; De Gracia, Rommel S. (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the level of awareness and practice of teachers in designing and implementing development projects, specifically research, innovation, and professional development (PD) initiatives, at Canabuan National High School as the basis for developing a coaching and mentoring program. Guided by the premise that awareness alone does not ensure successful implementation, the study was anchored on the concepts of professional support and participatory mentoring. A descriptive correlational research design employing quantitative and qualitative approaches was utilized. Total enumeration sampling was applied, involving all permanent teachers with at least one year of service during School Year 2024–2025. Data were collected using a validated researcher-made Likert-scale questionnaire, supplemented by open-ended questions, focused group discussions, and interviews. Quantitative data were analyzed using frequency, percentage, mean, standard deviation, and Pearson correlation, while qualitative responses were examined through open and axial coding. The findings showed that teachers possessed a very high level of awareness but a low level of practice in designing and implementing development projects. Most respondents had neither proposed nor implemented division-accepted research, innovation, or PD initiatives, and the relationship between awareness and practice was found to be very weak and statistically insignificant. The study further identified limited institutional support, heavy workload, inadequate mentoring, insufficient training opportunities, and limited access to research resources as major barriers to teachers’ participation. Based on these findings, the study concluded that continuous capacity-building, structured mentoring, institutional support, and sustained professional development are essential to strengthen teachers’ competencies and increase their engagement in development projects. The study recommends implementing school-based coaching and mentoring initiatives, including Project MENTOR, to enhance teachers’ research capabilities. The study aligns with Sustainable Development Goal (SDG) 4: Quality Education by promoting teacher capacity building and continuous professional learning. It also contributes to educational and institutional sustainability by strengthening school-based research culture and supporting continuous school improvement through effective development project implementation.